Evaluation on the fatigue behavior of sand-blasted AlSi10Mg obtained by DMLS - Annalisa Pola; Davide Battini; Marialaura Tocci; Andrea Avanzini; Luca Girelli; Candida Petrogalli; Marcello Gelfi (Fracture and Structural Integrity)
In the present paper, fatigue tests were performed on sand-blasted AlSi10Mg samples produced by Direct Metal Laser Sintering (DMLS). The effect of sand-blasting on surface properties was evaluated by roughness and residual stresses measurements, together with morphological analysis, in comparison with as-built condition. An evident improvement of surface finishing was observed after sand-blasting, which also leaded to the presence of compressive residual stress on the external surface of samples, as revealed by XRD2 measurements. Furthermore, defects analysis allowed the identification of a uniform distribution of porosities in the cross section in terms of number of defects, while larger porosities seem more abundant close to the surface. It was found that the tested material exhibits good fatigue resistance, supporting the positive role of sand-blasting as a simple post-processing treatment. Superficial defects are the preferential crack initiation sites, as demonstrated by SEM analysis of fracture surfaces.